The Effect of Product Quality and Price on Customer Loyalty through Customer Satisfaction - Deby Gunawan; Romauli Nainggolan; Effendi, Laij Victor (Jurnal Entrepreneur dan Entrepreneurship, 2024)
Increasingly fierce competition in the fashion industry resulted in apparel or retail companies having to maintain loyalty from customers. This study aimed to examine and provide an in-depth description of the formation of customer loyalty in terms of product quality and price mediated by customer satisfaction. Data was obtained by distributing online questionnaires using a purposive sampling method to 140 customers who had purchased products of UNIQLO in Surabaya for more than two times. Data was analyzed using the Structural Equation            Model – Partial Least Square (SEM-PLS) with the SmartPLS version 3.2.9. This study results that each product quality and price has a positive effect on customer satisfaction, customer satisfaction has a positive effect on customer loyalty, and product quality and price has a positive effect on customer loyalty, either directly or indirectly through the mediation relationship of customer satisfaction. Furthermore, this study also found that the effect of product quality on customer loyalty is on a similar level with the effect of price on customer loyalty. However, price effect on customer loyalty decreased with the mediation of customer satisfaction.